Biogas Plant Upgrade to CO2‐Free Technology: A Techno‐Economic Case Study. Issue 10 (10th August 2020) - Kutsay, Andrey; Kratky, Lukas; Jirout, Tomas
Abstract: A techno‐economic analysis was performed for a biogas plant with in‐built algae production. Degradation in the fermenter occurs under mesophilic conditions, to produce 605 Nm 3 t −1 TS of biogas and 343 Nm 3 t −1 TS of methane after 50 days. The biogas was combusted in a combined heat‐and‐power unit to produce heat and electricity. Cultivation of Chlorella vulgaris was done in co‐annular photo‐bioreactors, with an annual productivity of 107.5 t. For cultivation, both autotrophic and mixotrophic growth were assumed. Detailed mass and energy balances were done. For both conditions of algae growth, the results are approximately the same after a 30‐year payback period. Abstract : A biogas plant with in‐built algae production is introduced, comparing different nutrition techniques for algae cultivation. For each model, a process flow diagram was constructed and mass and energy balances were evaluated. Based on this, economic analyses including sensitivity analyses were made, showing the feasibility of the projects.